2005
DOI: 10.1128/jvi.79.15.9786-9798.2005
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of the Hepatitis B Virus Pre-S1 Domain Involved in Receptor Recognition

Abstract: Hepatitis B virus (HBV) and woolly monkey hepatitis B virus (WMHBV) are primate hepadnaviruses that display restricted tissue and host tropisms. Hepatitis D virus (HDV) particles pseudotyped with HBV and WMHBV envelopes (HBV-HDV and WM-HDV) preferentially infect human and spider monkey hepatocytes, respectively, thereby confirming host range bias in vitro. The analysis of chimeric HBV and WMHBV large (L) envelope proteins suggests that the pre-S1 domain may comprise two regions that affect infectivity: one wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
116
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(121 citation statements)
references
References 56 publications
3
116
0
1
Order By: Relevance
“…6,7 (3) The integrity of the N-terminal 77 amino acids is essential for infectivity, whereas the preS2 domain is dispensable. 8,9 (4) Acylated peptides comprising the Nterminal 47 amino acids of the preS1 domain abolish HBV infection in vitro [10][11][12][13] and in vivo (Petersen et al, unpublished observations, 2007).…”
mentioning
confidence: 99%
“…6,7 (3) The integrity of the N-terminal 77 amino acids is essential for infectivity, whereas the preS2 domain is dispensable. 8,9 (4) Acylated peptides comprising the Nterminal 47 amino acids of the preS1 domain abolish HBV infection in vitro [10][11][12][13] and in vivo (Petersen et al, unpublished observations, 2007).…”
mentioning
confidence: 99%
“…An early study which suggested that the preS2 portion of HBV might mediate binding of viral particles to hepatocytes (32) was determined to be false. Even though it has been well established that the preS1 is most critical for HBV infection there has not been a consensus on which region(s) of the preS1 is most critical for infection (14)(15)(16)(17)(18)(19)(20). In addition to the absence of structural knowledge on the preS1 domain another, perhaps more serious, bottleneck in delineating effective preS1 domains responsible for HBV attachment was the lack of an efficient cell culture assay system.…”
Section: Resultsmentioning
confidence: 99%
“…Even though the former utilizes a peptide fragment and the latter a small chemical compounds they both rely on the same strategy, blocking initial viral entry. In order to develop an anti-HBV agent following a similar strategy several investigators attempted to map the regions(s) of HBV surface proteins that would be crucial for the initial binding of HBV to a putative hepatocyte receptor (14)(15)(16)(17)(18)(19)(20). An early study which suggested that the preS2 portion of HBV might mediate binding of viral particles to hepatocytes (32) was determined to be false.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Los dominios más importantes del HBsAg son: el sitio de unión al receptor del hepatocito, aminoácidos 21-47 de la forma L, que además es esencial para el ensamble y salida de los viriones [25][26][27] ; el dominio ubicado entre los residuos 29-79 que forma el principal "loop" citoplasmático y mediante el cual interactúa con HBcAg; el dominio entre los aminoácidos 3-16 en la forma M, que se une al sitio de polimerización de la albumina, y la principal región hidrofílica, localizada entre los residuos 101-169 de la forma S, que incluye el determinante "a" (aminoácidos 124-147), el cual adquiere su conformación debido a dos puentes disulfuro [28][29] .…”
Section: Infectología Al Díaunclassified